Acute Administration of Calafate (Berberis Microphylla) Extract Induces the Expression of Thermogenic Markers and Modulates Gut Microbiota in Mice Fed a High-Fat Chow Diet - Poblete-Aro, C (S. Karger AG, 2024)
Introduction: Obesity, characterized by excess adipose tissue, is a major public health problem worldwide. Brown adipose tissue (BAT) and beige adipose tissue participate in thermogenesis through uncoupling protein 1 (UCP1). Polyphenols including those from Calafate (a native polyphenol-rich Patagonian berry), are considered as potential anti-obesity compounds due to their prothermogenic characteristics. However, polyphenols are mainly metabolized by the gut microbiota (GM) that may influence their bioactivity and bioavailability. The aim of this study was to determine the impact of dietary administration with a Calafate polyphenol-rich extract on thermogenic activity of BAT and beige adipose tissue and GM composition. Methods: Eight-week-old C57BL6 mice (n = 30) were divided into 4 groups to receive for 24 weeks a control diet (C), a high-fat diet alone (HF), or high-fat diet supplemented with Calafate extract (HFC) or the same high-fat diet supplemented with Calafate extract but treated with antibiotics (HFCAB) from week 19-20. Administration with Calafate extract (50 mg/kg per day) was carried out for 3 weeks from week 21-23 in the HFC and HFCAB groups. After euthanasia, gene expression of thermogenic markers was analyzed in BAT and inguinal white adipose tissue (iWAT). Transmission electron microscopy was performed to assess mitochondrial morphology and cristae density in BAT. GM diversity and composition were characterized by deep sequencing with the MiSeq Illumina platform. Results: Calafate extract administration had no effect on weight gain in mice fed a highfat diet. However, it prevented alterations in mitochondrial cristae induced by HFD and increased Dio2 expression in BAT and iWAT. The intervention also influenced the GM composition, preventing changes in specific bacterial taxa induced by the high-fat diet. However, the antibiotic treatment prevented in part these effects, suggesting the implications of GM. Conclusion: These results suggest that the acute administration of a Calafate extract modulates the expression of thermogenic markers, prevents alterations in mitochondrial cristae and intestinal microbiota in preclinical models. The study highlights the complex interaction between polyphenols, thermogenesis, and the GM, providing valuable insights into their potential roles in the treatment of obesity-related metabolic diseases. © 2024 The Author(s). Published by S. Karger AG, Basel.